Strategi Kontruktif Dan Dekonstruktif: Proses Identifikasi Pola Bilangan Mahasiswa Calon Guru SD - Nurmawanti, Iva; Radiusman, Radiusman; Haryati, Linda Feni; Sobri, Muhammad; Anar, Ashar Pajarungi (Pendidikan Matematika Universitas PGRI Yogyakarta, 2020)
This study aims to describe the process of identifying elementary student teacher candidates using constructive and deconstructive strategies. This study's research subjects were 6th-semester PGSD students of Mataram University who attended elementary mathematics learning courses. This type of research is a descriptive study with a qualitative approach. Data collected in the form of test results about patterns and interviews. Then the data is analyzed. The results of the data analysis showed that there was no difference between the process of identifying student patterns using either constructive or deconstructive strategies. The process carried out by students is seeing the shape of the image compiler, making rules for each image, then determining the next pattern rules based on the rules that have been made previously in each image.Keywords: pattern identification, constructive strategy, deconstructive strategy, figural pattern